(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
This paper aims at finding similarities between the epistemological thinking of Ortega and Popper with regard to a fundamental problem in the theory of knowledge, that is to say, the relationship between Observation and Theory. This relationship is examined both at the level of scientific knowledge and at the level of common sense knowledge, with emphasis on the main convergence between the two thinkers.